THE ROLE OF THE VILLAGE CONSULTATIVE BODY (BPD) IN SUPERVISING VILLAGE DEVELOPMENT: A CASE STUDY OF TOLONDADU I VILLAGE, BOLAANG MONGONDOW REGENCY - Moh Hamdi Hulukati; Karlina Napu; Titin Dunggio (Journal of Economic, Business, and Administration (JEBA), 2026)
The strategic implementation of horizontal checks-and-balances is a key determinant for transparent rural governance, yet it is often restricted by complex micro-level structural realities. This study aims to determine and analyze: (1) how the Village Consultative Body (BPD) operationalizes its sequential supervisory strategies over village administration and infrastructure planning, and (2) the multidimensional barriers that hinder the BPD from optimizing its horizontal check-and-balance function. Executed in Tolondadu I Village, Bolaang Uki District, South Bolaang Mongondow Regency, this study adopted a qualitative descriptive design. Data were collected through field observations, secondary documentation analysis, and semi-structured in-depth interviews using a purposive sampling technique with key informants, including the Village Head, BPD members, and local community representatives. The data were evaluated inductively using the interactive analysis model (data condensation, data display, and conclusion drawing) and validated through source and technical triangulation. The results indicate that: (1) the BPD formalizes its oversight through distinct structural phases (data collection, real-time concurrent monitoring, and post-activity assessment) across key village sectors such as infrastructure development, BUM Desa management, and asset mutations. When compliance errors occur, the BPD executes a four-stage sequential escalation protocol consisting of regulatory monitoring, persuasive warnings, internal clarification meetings, and executive escalation to the Camat and Bupati; (2) the optimization of this supervisory framework collapses into a superficial year-end bureaucratic formality due to a multidimensional bottleneck. This constraint is driven internally by severe capacity deficits linked to varied and low formal educational levels among BPD members, an absolute absence of regional technical guidance (Bimtek) from higher government tiers, and an internal breakdown of active member participation.